A critical analysis of newspaper editorial discourse on the portrayal of uprising in Libya and Syria - Afzal, Naeem; Harun, Minah (SAVAP International, 2015)
This research paper critically analyzed the editorial discourse of uprising in Libya and Syria from two mainstream newspapers namely The News International of Pakistan and the Arab News of Saudi Arabia.We explored how the crises were represented in the two cultural settings, how the news editorials satisfied the readership through the ideological framing and how that impacted the public opinion.The editorial texts were published during January 2011 to December 2012 which was a peak time for media coverage of the events. The theoretical framework of this study was based on van Dijk’s model of ideological square that served as a guiding principle for us to treat the editorial voices as in-group (Saudi Arabia) and out-group representations (Pakistan).We used the qualitative data analysis software package NVivo 10 to analyze the data.Findings of 12 editorial texts elucidated ‘evaluative beliefs’ of editors and their ideological constructions of authorities and protestors as social actors of the uprising. Drawing from the perspective of critical discourse analysis (CDA), we identified editorial relationship with the uprising through making sense of the meaning constructed.The study revealed that the editorials portrayed the authorities and their actions as a threat to incoming change and the protectors as indicators of revolution and social change.